2014
DOI: 10.1007/s00464-014-3631-6
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-bronchial fistula closed by endoscopic fistula plug (with video)

Abstract: Post-esophagectomy fistula is a morbid complication and the surgical treatments available are highly morbid and have variable success rates. Due to the development of new endoscopic technologies, the endotherapy has assumed new prominence for treatment of enteric fistula. This complex case illustrates feasibility of endoscopic fistula treatment using dual scope, biologic plug application which effectively controlled this patient's EBF symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As patients often present with malnutrition and repeated pneumonia, prompt administration of broad-spectrum antibiotics, gastric drainage, maintenance of fluid and electrolyte balance, and chest physiotherapy are necessary before definitive surgery. Even though there is no standard treatment for GBF, several interventions have been proposed in the past 20 years, such as esophageal stenting, tracheobronchial Y-shaped stenting, over-the-scope clips, fistula plugs, and surgical repair with muscle flaps or bovine pericardium [2,6,9,12–14] . Interestingly, Li et al have demonstrated that surgical repair has a greater long-term survival rate than other non-invasive treatments [10] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As patients often present with malnutrition and repeated pneumonia, prompt administration of broad-spectrum antibiotics, gastric drainage, maintenance of fluid and electrolyte balance, and chest physiotherapy are necessary before definitive surgery. Even though there is no standard treatment for GBF, several interventions have been proposed in the past 20 years, such as esophageal stenting, tracheobronchial Y-shaped stenting, over-the-scope clips, fistula plugs, and surgical repair with muscle flaps or bovine pericardium [2,6,9,12–14] . Interestingly, Li et al have demonstrated that surgical repair has a greater long-term survival rate than other non-invasive treatments [10] …”
Section: Discussionmentioning
confidence: 99%
“…Even though there is no standard treatment for GBF, several interventions have been proposed in the past 20 years, such as esophageal stenting, tracheobronchial Y-shaped stenting, over-the-scope clips, fistula plugs, and surgical repair with muscle flaps or bovine pericardium. [2,6,9,[12][13][14] Interestingly, Li et al have demonstrated that surgical repair has a greater long-term survival rate than other non-invasive treatments. [10]…”
Section: Literature Reviewmentioning
confidence: 99%
“…Endoscopic devices that are commonly used include stent, clips, plugs, fibrin glue, and vacuum-assisted closure sponge. [5][6][7][8][9][10][11] In this paper, we describe a case series of postesophagectomy GBF which were managed endoscopically using over-the-scope-clip (OTSC) (OTSC system; Ovesco Endoscopy AG, Tubingen, Germany).…”
Section: Introductionmentioning
confidence: 99%